COPD management according to old and new GOLD guidelines: an observational study with Italian general practitioners. (June 2014) - Maio, S.; Baldacci, S.; Martini, F.; Cerrai, S.; Sarno, G.; Borbotti, M.; Pala, A.P.; Murgia, N.; Viegi, G.; on behalf of the COMODHES study group
Abstract Background: Guideline recommendations for COPD management are only partially applied within primary care clinical practice. Objective: To compare the COPD management by Italian general practitioners (GPs) according to either the old GOLD (oGOLD) or the new GOLD (nGOLD) guidelines. Research design and methods: Observational study in different Italian areas. A total of 176 GPs enrolled their patients with a COPD diagnosis. Questionnaires were used to collect data on: COPD symptoms, disease severity, exacerbations, prescribed pharmacological and non-pharmacological treatments. COPD severity was estimated according to oGOLD and nGOLD guidelines. Results: A total of 526 subjects had complete information to assess COPD severity level according to guidelines (symptoms level, spirometry, history of exacerbations). The investigated subjects were more frequently males (71.2%) with a mean age of 72.5 years, and ex-smokers (44.4%). GPs reported sufficient control of the disease in 47.2% of the subjects with over two exacerbations in the last 12 months. Most patients have moderate COPD (51.5%), according to oGOLD, and belong to D groups (high risk, more symptoms) (45.6%), according to nGOLD. Overall, a low use of post-bronchodilator spirometry (65.1%) and of pulmonary rehabilitation (13.4%) was shown. The results highlighted a low prescriptive appropriateness but with higher value according to nGOLD than oGOLD: 61.4% vs 35.6%. Study limitations: Prescription data only provide limited information to judge prescribing quality, thus the results have to be evaluated with caution; moreover, this study was not designed to assess the difference between oGOLD and nGOLD. Conclusions: Guideline recommendations are applied only partially within clinical practice. A higher prescriptive appropriateness is shown by GPs using nGOLD classification. This might be due to the fact that nGOLD, with respect to oGOLD, takes into account anamnestic usual features considered by GPs in their clinical practice.